Improvement of water use efficiency in pomegranate (Punica granatum) cv. Bhagwa under micro-irrigation system - MESHRAM, D T; SINGH, N V; PAL, R K (The Indian Journal of Agricultural Sciences, 2016)
A field experiment was conducted to evaluate the effect of different irrigation levels (10 to 50 and 20 to 60%) and mulches (No mulch, dry lawn mulch, dry lawn mulch + hydrogel and hydrogel alone) on growth and yield of Bhagwa pomegranate (Punica granatum L.). The actual pomegranate evapotranspiration in l/day/tree was estimated by using the reference crop evapotranspiration, pan coefficient, crop coefficient, wetted area, area occupied by one tree and micro-irrigation efficiency. The study revealed that mulch + hydrogel enhanced vegetative growth and yield contributing characteristics. However, 30 and 40% irrigation levels for three and four years pomegranate plants, respectively, produced results at par with respect to yield attributing traits, quality, juice content and TSS. Based on statistical analysis of vegetative and yield characteristics, it was inferred that the treatment combination comprising of dry lawn mulch + hydrogel and irrigation levels at 30 and 40% with alternate day irrigation resulted into higher yield with good quality fruits as compared to other treatments.